Розроблення евакуаційних заходів за результатами розрахунку індивідуального пожежного ризику - Залуцький, Мар'ян Володимирович; Zalutskyi, Marian (Національний університет "Львівська політехніка", 2025)
Сьогодні пожежна безпека, охорона та захист від природних загроз є невід'ємною частиною сучасної стратегії виживання, сталого розвитку та конкурентоспроможності. Порятунок людських життів є найважливішою метою протипожежного захисту. Належні плани евакуації мають важливе значення для досягнення цієї мети. Можна розглянути два методи: Перший – це нормативний метод, який враховує заповнюваність, розмір і кількість виходів, а також максимальну довжину шляхів евакуації; Другий – це метод продуктивності, який стосується максимального часу, необхідного для евакуації. Перший метод базується на трьох основних моментах: – щільність людей; – потік людей; – довжина та ширина шляхів евакуації. Другий метод визначає, чи є необхідний час евакуації меншим за наявний час безпечного виходу. Основна мета – надати обґрунтовану підтримку стратегії евакуації, щоб усі люди, які перебувають у будь-якій точці споруди, могли евакуюватися у безпечне місце. Метою БКР є аналіз інженерії пожежної безпеки при евакуації людей з будівель. У роботі обґрунтовано, що точне визначення часу евакуації є критично важливим для забезпечення безпеки людей у надзвичайних ситуаціях. Розглянуто два сценарії: консервативний (з урахуванням максимальної дистанції та потенційних затримок) і оптимістичний (за відсутності черг та обмежень руху). Зазначено, що ручні розрахунки недостатні при складних умовах евакуації, наприклад, коли потоки людей зливаються з кількох корпусів. У таких випадках рекомендовано застосування імітаційних моделей для точнішого прогнозування. Робота демонструє, що рецептурні (нормативні) методи є застарілими для складних об’єктів і не враховують поведінкових та фізіологічних особливостей людей. Інженерний підхід дозволяє адаптувати евакуаційні рішення до конкретного об'єкта та сценарію пожежі шляхом розрахунку ASET і RSET та використання сучасного програмного забезпечення. Підкреслено, що інвестиції в пожежну безпеку мають бути економічно обґрунтованими. Економічну ефективність технічних рішень слід розглядати з урахуванням не лише витрат, а й поліпшених характеристик нової техніки, що оцінюється через коефіцієнт еквівалентності.

The analysis of the dynamics of industrial accidents showed that by type, the largest number of accidents occurred due to fires and explosions (67), which, together with transport accidents (39) and accidents in life support systems (20), account for 82% of the total number of industrial accidents. The use of natural gas in boiler houses creates the possibility of an explosive cloud, the possibility of a natural gas explosion and gas burning in the form of a ‘fireball’ on the territory of the boiler house and in its premises. The following types of accidents are typical in boiler rooms: explosion (detonation combustion) - combustion of pre-mixed gas-air clouds with supersonic speeds in a closed volume and flash - a flame wave, combustion of pre-mixed gas-air clouds with subsonic speeds in an open space or confined space. The greatest danger to people and property is posed by the impact of explosions and fireballs. The purpose of the ICR is to analyse the hazards of the boiler house of the residential area Ryasne-2 of LLC «Energy Saving Technologies», Lviv, and to develop measures to improve its industrial safety. The analysis of boiler house operation showed that the most common causes of accidents are malfunctions of the burners, gas supply system, damage to boiling and screen pipes, flue lining and combustion chamber. In the event of an explosion in the boiler room and on the territory of the boiler house when the gas pipeline is depressurised, significant damage to equipment, communications and the boiler house building is possible. Adjacent production facilities may suffer light and medium damage to building elements, equipment, and glazing. If there is an ignition source, a secondary consequence is the development of a fire. An explosion usually results in a fire. Ignition of a mixture of methane vapours and air occurs when an ignition source is present and when the concentration of flammable vapours in the vapour-air mixture is greater or less than the explosive concentration. The purpose of the ICR is to analyse the hazards of the boiler house of the residential area Ryasne-2 of LLC ‘Energy Saving Technologies’, Lviv, and to develop measures to improve its industrial safety. The analysis of boiler house operation showed that the most common causes of accidents are malfunctions of the burners, gas supply system, damage to boiling and screen pipes, flue lining and combustion chamber. In the event of an explosion in the boiler room and on the territory of the boiler house when the gas pipeline is depressurised, significant damage to equipment, communications and the boiler house building is possible. Adjacent production facilities may suffer light and medium damage to building elements, equipment, and glazing. If there is an ignition source, a secondary consequence is the development of a fire. An explosion usually results in a fire. Ignition of a mixture of methane vapours and air occurs when an ignition source is present and when the concentration of flammable vapours in the vapour-air mixture is greater or less than the explosive concentration. Accidents may occur in the boiler house related to the combustion of gaseous fuel and damage to the drum, screen boiler and economiser tubes of DKVR-6,5-13 steam boilers. The conditions for such accidents are violations of the boilers' operation mode, external factors, errors and inattention of the operating personnel. The main causes of accidents in this boiler room are human error, increased system pressure and equipment damage. They can lead to an explosion in the boiler room or the formation of a ‘fireball’. This can result in the ignition of objects inside and outside the boiler room, fire and destruction of adjacent buildings, as well as injuries to boiler room personnel and residents of the neighbourhood. In order to improve the technogenic and fire safety of the boiler house, reduce the scale of a possible accident, promptly respond to and prevent emergencies, it is proposed to install a methane sensor DM-14, which is designed to notify of the formation of an explosive mixture in the boiler room when the methane concentration exceeds the established standards, which contributes to the early detection of an explosion threat, and a carbon monoxide sensor DCG-14 is designed to notify of the excess of carbon monoxide concentration above the established thresholds.
Development of evacuation measures based on the results of individual fire risk calculation
Keywords: 8.263.00.01; активні заходи протипожежного захисту; розрахунковий сценарій пожежі; шлях евакуації; доступний час безпечної евакуації (ASET); необхідний час безпечної евакуації (RSET); вихід (пожежний аварійний вихід); пожежна сигналізація; пожежний сповіщувач; рівень пожежного ризику. Перелік скорочень: НС – надзвичайна ситуація; ASET – доступний час безпечної евакуації; RSET – необхідний час безпечної евакуації; СЗЗ – санітарна захисна зона; ПНО – потенційно небезпечний об’єкт; ПЛАС– план ліквідації аварійної ситуації; ППЗ – протипожежний захист; МВЗ – можлива вибухонебезпечна зона; boiler room; potentially dangerous object; methane; gas control point; water heating boiler; pipeline depressurization; explosion of gas mixture; epicenter of the explosion; fireball; destruction zones; contusion; equipment hazard card; localization and liquidation of the accident. List of abbreviations: EM - Emergency; CP – Civil Protection; Commission TG and ESE – commission on technogenic and ecological safety and emergencies PDO – potentially dangerous object; UGS - gas control cabinet point; CH4 - methane; MPC - maximum permissible concentration; PPE - personal protective equipment; PUH - air shock wave; MVZ - possible explosive zone; KVP - control and measuring device